(untitled) (Journal of the College of Basic Education, 2025)
This research aims to identify (the effect of the learning windows strategy in developing reading comprehension for the Arabic language subject among second-year middle school students), and to achieve this, the researcher chose a sample of (71) second-year middle school students in (Zohour Al-Iraq Secondary School) affiliated to the First Rusafa Education Directorate, with (36) students for the experimental group and (35) students for the control group. The researcher rewarded the students of the two research groups in the variables of chronological age calculated in months and the academic achievement of parents, and the intelligence test. After the researcher identified the scientific material and formulated the behavioral objectives, their final number reached (93) behavioral objectives. The researcher prepared model teaching plans for each of the topics specified for the experiment. In order to measure reading comprehension among the students of the two research groups, the researcher prepared a reading comprehension test with (38) test paragraphs, the validity and reliability of which were verified. After applying the research tool and analyzing the results obtained by the researcher Statistically, the results showed that the experimental group outperformed the control group in the reading comprehension test. The researcher also concluded the effectiveness of the learning windows strategy in reading comprehension among second-year middle school students in reading topics compared to the traditional method. The researcher also recommended benefiting from the results of this research by moving away from old teaching methods in teaching reading topics.